2022
DOI: 10.3390/antibiotics11111646
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In Vitro Activity of Double-Carbapenem Combinations against KPC-2-, OXA-48- and NDM-Producing Escherichia coli and Klebsiella pneumoniae

Abstract: Double-carbapenem combinations have shown synergistic potential against carbapenemase-producing Enterobacterales, but data remain inconclusive. This study evaluated the activity of double-carbapenem combinations against 51 clinical KPC-2-, OXA-48-, NDM-1, and NDM-5-producing Escherichia coli and Klebsiella pneumoniae and against constructed E. coli strains harboring genes encoding KPC-2, OXA-48, or NDM-1 in an otherwise isogenic background. Two-drug combinations of ertapenem, meropenem, and doripenem were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
1
1
Order By: Relevance
“…The synergistic effect of double‐carbapenem combination has been reported against K. pneumoniae and P. aeruginosa . 30 Although a previous study showed a considerable decrease in MICs of MER in combination with doripenem, 31 the low frequency of significant amounts of FICI in our study demonstrates that using double‐carbapenem combination as a treatment choice for carbapenem‐resistant Gram‐negative bacteria is not always appropriate. However, FICI amounts of MER‐IMI were significant in isolates lacking MBL enzymes.…”
Section: Discussioncontrasting
confidence: 61%
“…The synergistic effect of double‐carbapenem combination has been reported against K. pneumoniae and P. aeruginosa . 30 Although a previous study showed a considerable decrease in MICs of MER in combination with doripenem, 31 the low frequency of significant amounts of FICI in our study demonstrates that using double‐carbapenem combination as a treatment choice for carbapenem‐resistant Gram‐negative bacteria is not always appropriate. However, FICI amounts of MER‐IMI were significant in isolates lacking MBL enzymes.…”
Section: Discussioncontrasting
confidence: 61%
“…The isolate UTA41 co-harbor the OXA-10-type class D β-lactamase and the KPC-2-type class A β-lactamase. This co-carriage was observed on different studies of Klebsiella pneumoniae from clinical origin on Sweden, Taiwan, and Russia [ [34] , [35] , [36] ]. KPC-2 has become the most clinically important carbapenemases enzyme due to its prevalence in enteric bacteria from human, animal and environmental origin [ [37] , [38] , [39] ].…”
Section: Discussionmentioning
confidence: 62%